FEATURES OF BIODIVERSITY CONSERVATION UNDER THE SPREAD OF INVASIVE SPECIES OF WEEDS: ANALYSIS AND PROSPECTS - Korpita, H.; Shuvar, I.; Dudar, I.; Palii, D.; Hadzalo, O. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Invasive plants can cause significant damage to agriculture, forestry and water management, as well as to protected areas, threatening human and animal health. The disappearance of native plant species leads to a loss of biodiversity and can provoke ecological imbalances. Ukraine is characterized by a high level of spread of invasive plant species, which reinforces the need to take measures for their control and management. It has been noted that the disappearance of native plant species leads to the disappearance of native species of animals, fungi, and many microorganisms that have been building links with the native flora for thousands or millions of years, are directly dependent on it, and are organically interconnected. That is why the invasion of an alien species does not increase the number and activity of local biodiversity, but, on the contrary, leads to the death of a significant number of flora and fauna species dominated by only one or a few alien species. In Ukraine, the impact of non-native plants on the environment is increasing every year. According to the level of adventitization of flora, Ukraine occupies a prominent place among other floras of the world. The spontaneous fraction of adventitious flora of Ukraine includes 830 species of vascular plants (including 18 % – archaeophytes and 82 % – xenophytes), which is about 14 % of the total number of flora species of the country, which has more than 6,000 species of vascular plants (including all aboriginal and adventive species), as well as the main cultivated and wild plants. As a result of the study of the effect of herbicides on the Canadian goldenrod (Solidago canadensis L.), it was established that all three investigated herbicides – Lintur 70 WG, Dianat and Roundup Max – effectively reduce the population of this plant. However, it was found that the effectiveness of herbicides increases over time, which may be due to longer exposure of the substance to plants. Herbicides Lintur 70 WG and Roundup Max showed higher efficiency compared to Dianat. In addition, it was established that all three investigated herbicides have a significant effect on the dry mass of Solidago canadensis L. plants on the 60th day after their application, confirming the high efficiency of their use. Therefore, the study results emphasize the importance of considering the timing of herbicide treatments to ensure long-term protection of cultivated plants from weeds.